Atmospheric stress corrosion crack growth rates of 316 L stainless steel for nuclear waste containment. (December 2020) - Zhang, Y.; Cook, A.J.M.C.; Padovani, C.; Zhou, S.; Turnbull, A.
Highlights: In situ high resolution (10 −13 m/s) crack growth measurements of atmospheric SCC established. Effect of humidity under MgCl2 deposits at 40 °C on crack growth rates evaluated. Drying and rewetting represents a severe exposure condition for SCC. Crack growth rate decayed with increasing humidity and crack depth. Abstract: Atmospheric stress corrosion cracking (SCC) tests were conducted for a 316 L stainless steel (SS) at an applied stress of 1.1 σ0.2 with a chloride deposition density of approximately 100 μg/cm 2 deposited as MgCl2 from solution. The test specimens were exposed in an atmospheric chamber at a constant temperature of 40 °C with initial relative humidity (RH) of 40 %, followed by an increase to 60 % RH, then 80 % RH, and finally a decrease to 60 % RH. The total exposure period was 6500 h (about 9 months). The stress corrosion crack growth rate decreased with increasing RH and with increasing crack depth.